Assentamentos Chico Mendes de Presidente Médici/Rondônia: terras marcadas por disputas (1996-2022) - Soares, Luciana Ribeiro Pinto (2024)
This project has to produce a historical analysis of the formation of the Chico Mendes Settlement, founded by the Landless Workers Movement (MST) in 1996, in the municipality of Presidente Médici, in Rondônia. In order to understand the contradictions involved in the agrarian issue in Brazil, especially in the particularities presented in Rondônia. With the emergence of the Landless. Movement, as a result of the processes of land appropriation and expropriation of peasants, ideological disputes between the MST and the economic relations of agribusiness in the settlement areas will be analyzed throughout the studies. The methodology chosen in this qualitative research, which sought to extract the local socioeconomic reality, documentary sources and interviews, as well as the historical expressions of power of economic groups, which operate in State structures, suppressing the actions of groups of individuals, who rebel against the current order and try to build spaces with other possibilities for economic, social and cultural production. When contextualizing the historical dynamics of the process of struggle for land today, it is clear that the correlations of forces that act in these spaces occur unequally. Given the dynamic nature of these forces, understanding how they work makes it necessary to produce new critical interpretations. However, the contradictions generated within society cannot hide the history of some significant social achievements as a result of the actions of individuals, collectively organized in pursuit of common goals. In this way, the reflections presented recognize the urgency of changing the behavior of human beings in the face of economic structures that seek to silence the voices of individuals and social organizations such as the MST, which place on the agenda of Brazil's economic policy,a proposal for agrarian reform. incorporated into the ideas of emancipation of individuals, so that social relations of production contribute to practices that respect diversities and adversities.